-3(m- 2n) = 5m please show the steps

Algebra
Tutor: None Selected Time limit: 1 Day

solve for m

Oct 3rd, 2015

Hello!

First, open parenthesis (distributive property):

(-3)*m - (-3)*(2n) = 5m, or
-3m + 6n = 5m   (associative property for multiplication).

Then, add 3m to the both sides:

3m - 3m + 6n = 3m + 5m, or
6n = 8m.

Finally, divide both sides by 8 and obtain

m = 6n/8 = 3n/4.

Or m = (3/4)n.

Please ask if something is unclear.
Sep 18th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Oct 3rd, 2015
...
Oct 3rd, 2015
Dec 6th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer